Pelatihan Batik Cap Dalam Rangka Meningkatkan Kreativitas Pengunjung Rumah Batik Komar Kota Bandung - Yuliarti, Iluh; Jaya, Asep Sutra; Herawati, Helmi (Jurnal Dehasen Mengabdi, 2022)
Batik training is given to visitors aimed at increasing knowledge, experience and creativity as well as having skills in the world of work and can open up opportunities in entrepreneurship. The stamped batik referred to in this case is batik made by stamping using a stamping tool such as a large stamp made of copper that has been designed with a certain motif with dimensions of 20cm x 20cm. Through this training activity, it is hoped that the visitors to the Komar Batik House can develop themselves and be creative in making various forms of stamped batik products according to the wishes and abilities of each of the visitors to the Komar Batik House. The stamped batik training is carried out with various approaches such as through the lecture method, question and answer and practice or practice of making stamped batik directly. Activities are carried out in various stages from the design to the product manufacturing process. The products that have been produced by the Komar Batik House are ties, blouses, shirts and other products.